Rubiaceae in Brazilian Atlantic Forest remnants: floristic similarity and implications for conservation - Marques de Paiva, Alessandra (2016)
Brazil holds most of the Atlantic Forest Domain and is also one of the Rubiaceae diversity centers in the Neotropics. Despite the urban expansion in the state of Rio de Janeiro, large areas of continuous vegetation with high connectivity degree can still be found. Recently, new Rubiaceae species have been described in the Rio de Janeiro flora, which present small populations and very particular distribution. The current paper analyzed the similarity in the floristic composition of the Rubiaceae in eight Atlantic Forest remnants of Rio de Janeiro state protected by Conservation Units. We also surveyed and set guidelines for conservation of microendemic species. The similarity analysis were based on previously published studies in Área de Proteção Ambiental de Grumari, Área de Proteção Ambiental Palmares, Parque Estadual da Serra da Tiririca, Parque Nacional do Itatiaia, Parque Nacional de Jurubatiba, Reserva Biológica de Poço das Antas, Reserva Biológica do Tinguá and Reserva Ecológica de Macaé de Cima - using the PAST software ("Paleontological Statistics") with Sørensen coefficient. The floristic similarity analysis revealed two groups with distinct physiographic characteristics and different vegetation types. Group A consisted in two Restinga areas, Área de Proteção Ambiental de Grumari and Parque Nacional de Jurubatiba, which showed strong bootstrap support (98 %). Group B included forest remnants with distinct phytophisiognomies or altitudes, but with moderate bootstrap support. Low similarity levels among the eight areas were found due to the habitats’ heterogeneity. The current study pointed out 19 microendemic species from the Atlantic Forest, they present a single-site distribution or a distribution restricted to Mountain and Metropolitan regions of Rio de Janeiro state. Concerning the conservation status of microendemic species, discrepancies between the Catalogue of Flora of Rio de Janeiro and the Red Book of Brazilian Flora (two of the main reference catalogs of Brazilian flora) have been identified. We have also highlighted the need for recollecting microendemic species from the Atlantic Forest, and for properly assessing the degree of threat faced by these taxons early.